LEGAL ISSUES OF IMPROVING HEALTH INSURANCE IN THE REPUBLIC OF UZBEKISTAN (American Journal of Business Management, Economics and Banking, 2023)
In the field of human health, it is important to make medical services affordable in all respects, high quality and financially affordable for the population. In the provision of medical services, the organization of the relationship between the medical institution, the doctor and the patient, the creation of the necessary conditions for the treatment of patients in the medical institution is organized in different ways. One of the most effective of these methods in modern medicine today is health insurance. Through health insurance, the insurance company takes all organizational (financially hospitalized, highly qualified doctors) financial measures related to the treatment of the insured person (patient) in the event of an insured event, and as a result the insured person has access to qualified and quality medical care. Today, there are no clear approaches to the role of health insurance in legal regulation and jurisprudence, which area of insurance it is: life insurance and general insurance. This at the same time creates a number of problems and gaps in the legal regulation of the interpretation of the essence of the health insurance contract and its application. Therefore, it is important to determine the essence of health insurance, its content and specifics as a legal relationship, and thus create a legal basis for health insurance.